(untitled) (Palíndromo, 2022)
This article reviews the recent publication of Richard and Mary Rouse’s investigation of the French illuminators between 1500 and 1715 and the new information brought to light regarding the evolution of their profession, their daily life and their integration into the Parisian artistic community. In doing so, further elements and reflexions are added, regarding the semantic evolution of the word enlumineur compared with the new word miniaturiste appearing in the early 17th century vocabulary and Parisian cultural world.